Comparison of the Effect of Ketorolac and Betamethasone Injection on Post Complications of Third Molar Surgery (A Clinical Trial) - Neda Omidpanah; Parnian Tarabosi; Hamed Nazari (University Library System, University of Pittsburgh, 2024)
BACKGROUND: The aim of this study was to evaluate the effect of preoperative ketorolac and betamethasone injections on reducing postoperative complications mandibular third molar surgery. MATERIALS AND METHODS: In this randomized clinical trial, 134 patients at the age group of 18-40 years who required mandibular molars surgery were studied. Patients were randomly divided into two groups. In A group, 1 mL of betamethasone LA was injected into the master muscle before surgery, and in the A group, 30 mg of ketorolac per 1 mL was injected before surgery. On the second and seventh days after surgery, patients were evaluated for the variables of maximum mouth opening, pain, swelling, and general satisfaction with the surgery through telephone calls on the second and seventh days. Independent t-test and Mann-Whitney test were used to evaluate the variables. RESULTS: The mean of pain intensity and the swelling variables in the betamethasone group were lower than the ketorolac group in second and seventh days (P<0.05). The mean of maximum mouth opening and the patient satisfaction variables in the betamethasone group were higher than the ketorolac group in second day (P<0.05). There was no statistically significant difference in the patient satisfaction and maximum mouth opening variables on the seventh day (P>0.05). CONCLUSION: This study concluded that betamethasone performed significantly better in reducing swelling, pain, maximum mouth opening limitation, and general satisfaction.